Catalogue of the type-species of the genera of the Cerambycidae, Disteniidae, Oxypeltidae and Vesperidae (Coleoptera) of the Neotropical Region - Monné, Miguel A. (Zootaxa, 2012)
The present list includes all available names, both valid and invalid, and the type-species of the genera and subgenera ofCerambycidae, Disteniidae, Oxypeltidae and Vesperidae (Coleoptera) of the Neotropical Region. Two new family-groupnames are proposed: Neoibidionini (type-genus: Neoibidion, a replacement name for Ibidion Audinet-Serville, 1834, ju-nior homonymy of Ibidion Gory, 1833) for Ibidionini Thomson, 1861 and Proholopterini (type-genus Proholopterus, areplacement name for Holopterus Blanchard, 1851, junior homonymy of Holopterus Brehm, 1845) for Holopterini La-cordaire, 1868. Oideterus Thomson, 1857a:15 is revalidated with the type-species, Oideterus buquetii Thomson, 1857 (bymonotypy). Udeterus Thomson, 1858b:515 is a junior synonym of Oideterus Thomson, 1857. Acanthocornis Monné &Monné, 2011 (Prioninae, Meroscelisini) is a new synonym of Hyleoza Galileo, 1987 and Acanthocornis flavus Monné &Monné, 2011 = Hyleoza confusa Tavakilian & Galileo, 1991. The genus Acanthocornis Monné & Monné, 2011 was erro-neously described in the tribe Anacolini. Acanthinodera Hope, 1834 is considered a nomen protectum and hereafter usedas valid genus name. Amallopodes Lequien, 1833 is a nomen oblitum consequently invalid name. Hephaestion (?) zikaniMelzer, 1923 is designated as the type-species of Parahephaestion Melzer, 1930; Corynellus mimulus Bates, 1885 as thetype-species of Corynellus Bates, 1885; Cosmius ochraceus Perty, 1832 as the type-species of Cosmius Perty, 1832 non Cosmius Dumeril, 1806, Diptera, and Alampyris nigra Bates, 1881 as the type-species of Alampyris Bates, 1881.